Budget Absorption's Effectiveness: Budget Implementation Commitment, Human Resource Capabilities, And Budget Planning Accuracy - Cris Kuntadi; Lia Puspasari (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This article reviews the variables that affect budget absorption effectiveness (Y), which functions as a dependent variable on budget planning accuracy (X1), human resource capabilities (X2), and budget execution commitment (X3), which serves as an independent variable. This article aims to develop a hypothesis for further investigation by showing how different variables interact. The literature review in this article shows the relationship between the accuracy of budget planning (X1) and the effectiveness of budget absorption (Y), the capabilities of human resources (X2) and the effectiveness of budget absorption (Y), and the commitment to budget implementation (X3) and the effectiveness of budget absorption (Y)